ROMEO AND JULIET - Shakespeare, William, 1564-1616.; Street, Helen; Cheung, Charly (Berkshire, U.K. : Baker Street Press, 2018)
What could be worse than falling in love with your enemy?
Keywords: Children's stories, English; English fiction